Severe vitamin D deficiency in chronic renal failure patients on peritoneal dialysis - (:unkn) unknown (DUSTRI-VERLAG DR KARL FEISTLE, 2006)
The aim of this study was to evaluate the prevalence of vitamin D deficiency in chronic renal failure (CRF) patients on peritoneal dialysis (PD) and to correlate the findings with various demographic and renal osteodystrophy markers. Method: This cross-sectional, multicenter study was carried out in 273 PD patients with a mean age of 61.7 +/- 10.9 years and mean duration of PD 3.3 +/- 2.2 years. It included 123 female and 150 male patients from 20 centers in Greece and Turkey, countries that are on the same latitude, namely, 36 - 42 degrees north. We measured 25(OH)D-3 and 1.25(OH)(2)D-3 levels and some other clinical and laboratory indices of bone mineral metabolism. Results: Of these 273 patients 92% (251 patients) had vitamin D deficiency i.e. serum 25(OH)D-3 levels less than 15 ng/ml, 119 (43.6%) had severe vitamin D deficiency i.e. serum 25(OH)D-3 levels, less than 5 ng/ml, 132 (48.4%) had moderate vitamin D deficiency i.e. serum 25(OH)D3 levels, 5 - 15 ng/ml, 12 (4.4%) vitamin D insufficiency i.e. serum 25(OH)D3 levels 15 - 30 ng/ml and only 10 (3.6%) had adequate vitamin D stores. We found no correlation between 25(OH)D-3 levels and PTH, serum albumin, bone alkaline phosphatase, P, and Ca x P. In multiple regression analyses, the independent predictors of 25(OH)D-3 were age, presence of diabetes (DM-CRF), levels of serum calcium and serum 1.25(OH)(2)D-3- Conclusion: We found a high prevalence (92%) of vitamin D deficiency in these 273 PD patients, nearly one half of whom had severe vitamin D deficiency. Vitamin D deficiency is more common in DM-CRF patients than in non-DM-CRF patients. Our findings suggest that these patients should be considered for vitamin D supplementation.
Keywords: vitamin D deficiency; serum 25(OH)D; dialysis; chronic renal failure; D INSUFFICIENCY; PARATHYROID-HORMONE; HYPOVITAMINOSIS-D; OSTEODYSTROPHY; HYPERPARATHYROIDISM; PREVALENCE; CALCIUM; KIDNEY; BONE; AGE